A Simulation-based PPE orientation training curriculum for novice physicians - Spencer W. Greaves; Scott M. Alter; Rami A. Ahmed; Kate E. Hughes; Devin Doos; Lisa M. Clayton; Joshua J. Solano; Sindiana Echeverri; Richard D. Shih; Patrick G. Hughes (Elsevier, 2023)
Summary: Background: Personal protective equipment (PPE) is effective in preventing coronavirus disease (COVID-19) infection. Resident knowledge of proper use and effective training methods is unknown. We hypothesise that contamination decreases and knowledge increases after a formalised PPE educational session. Methods: Participants included first year interns during their residency orientation in June 2020. Before training, participants took a knowledge test, donned PPE, performed a simulated resuscitation, and doffed. A standardised simulation-based PPE training of the donning and doffing protocol was conducted, and the process repeated. Topical non-toxic highlighter tracing fluid was applied to manikins prior to each simulation. After doffing, areas of contamination, defined as discrete fluorescent areas on participants' body, was evaluated by ultraviolet light. Donning and doffing were video recorded and asynchronously rated by two emergency medicine (EM) physicians using a modified Centers for Disease Control and Prevention (CDC) protocol. The primary outcome was PPE training effectiveness defined by contamination and adherence to CDC sequence. Results: Forty-eight residents participated: 24 internal medicine, 12 general surgery, 6 EM, 3 neurology, and 3 psychiatry. Before training, 81% of residents were contaminated after doffing; 17% were contaminated after training (P<0.001). The most common contamination area was the wrist (50% pre-training vs. 10% post-training, P<0.001). Donning sequence adherence improved (52% vs. 98%, P<0.001), as did doffing (46% vs. 85%, P<0.001). Participant knowledge improved (62%-87%, P <0.001). Participant confidence (P<0.001) and preparedness (P<0.001) regarding using PPE increased with training. Conclusion: A simulation-based training improved resident knowledge and performance using PPE.